A GRASP Approach to the Container Loading Problem - Moura, Ana (2005)
In this paper a new GRASP algorithm for the single Container Loading Problem is presented. The Container Loading Problem aims the packing of a set of boxes into a container, so that the wastes space is minimised and other side constraints related to the physical loading and transportation of the boxes are satisfied. Special attention will be paid to cargo stability issues. This GRASP algorithm is based on a “wall building” constructive heuristic and aims to achieve high levels of cargo stability without compromising the container volume utilization. The performance of this GRASP approach is evaluated both in terms of volume utilization and load stability and compared with well-known algorithms from the literature. This new approach proves to be rather effective in the sense that there are no other approaches that can produce solutions that are simultaneously better in terms of volume utilization and better in terms of cargo stability.